Analysis of Accounting Treatment for Musyarakah Financing in Capital Loan Transactions to Buy a House at Bank Syariah Indonesia KCP Medan Djuanda - Widya Yunisa; Rahmat Daim Harahap; Syawla Andina Auliya; Jihan Reswita; Faras Abiyu Zhafran; Anggun Debana Maharani (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2023)
Contribution: Where can this research be useful? Name the area, discipline, and so on. This study aims to analyze the accounting treatment of Musyarakah financing in home buying capital loan transactions at Bank Syariah Indonesia KCP Medan Djuanda. The method used is a qualitative approach with data collection techniques through interviews and documents. The results show that Bank Syariah Indonesia uses Sharia principles in conducting Musyarakah financing transactions, such as feasibility checks, asset selection, financing according to the percentage of ownership, sharing of profits and losses according to the proportion of ownership, payment of principal installments and periodic profit sharing. In addition, Bank Syariah Indonesia also carries out Sharia supervision duties through the Sharia Supervisory Board and the Sharia Supervisory Division. However, several obstacles were also found in the process of borrowing capital to buy a house with Musyarakah financing, such as a lack of competent human resources, a lack of public understanding of Islamic financing products, and differences in perceptions between Indonesian Islamic Banks and customers regarding the benefits and risks of Musyarakah financing products. The implementation of Musyarakah financing must be carried out carefully and transparently in order to create trust from the public. The results of the study show that Bank Syariah Indonesia applies accounting principles that are in accordance with sharia principles in providing Musyarakah financing. The accounting treatment carried out includes recording transactions, profit and loss sharing, and financing settlements. Recording of transactions is carried out using special accounts for Musyarakah financing, while the distribution of profits and losses uses the principles agreed upon at the beginning of the transaction..